The Cost of Honesty: Does CSR Expenditure Signal Corruption Transparency in the Financial Firms? - Dewi Mustika Ratu (DINASTI RESEARCH, 2026)
This study investigates the relationship between CSR spending and anti-corruption disclosure. Through the lens of impression management, higher CSR expenditure encourages firms to seek more disclosures, especially regarding anti-corruption, as a strategy to build a positive impression among stakeholders. This research employs a sample of financial firms listed in the Indonesia Stock Exchange (IDX) during 2021-2024, with 200 firm-year observations. Data were collected from the annual and sustainability reports through archival research. As expected, there is a positive relationship between CSR spending and anti-corruption disclosure. Higher CSR spending motivates firms to reveal anti-corruption activities to establish a good reputation. Besides being a regulatory requirement, anti-corruption disclosures also serve as a strategic action in impression management. Consequently, regulators need to go beyond CSR spending regulations to determine whether companies’ disclosures reflect genuine ethical commitments or serve as symbolic gestures.